Endovascular Treatment of Epistaxis in Patients with Hereditary Hemorrhagic Telangiectasia - Layton, K.F.; Kallmes, D.F.; Gray, L.A.; Cloft, H.J. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: The treatment of epistaxis in patients with hereditary hemorrhagic telangiectasia can be very challenging. The purpose of our study was to evaluate our experience with endovascular epistaxis embolization in patients with hemorrhagic hereditary telangiectasia and to compare this with our experience in patients treated for idiopathic epistaxis.MATERIALS AND METHODS: Over a 6-year period, we treated 22 patients with epistaxis by using endovascular embolization. Twelve of 22 patients had hereditary hemorrhagic telangiectasia; 10 patients had idiopathic epistaxis. The angiographic findings, efficacy of treatment, and complications for both groups were compared.RESULTS: Patients with hereditary hemorrhagic telangiectasia had angiographic abnormalities in 92% of cases compared with only 30% in the idiopathic epistaxis group. Compared with a group of 10 patients treated for other causes of epistaxis, those with hereditary hemorrhagic telangiectasia required significantly more re-embolization treatments or additional surgical procedures because of continued or recurrent bleeding episodes after embolization (P = .03). Complications were rare; a single patient in the idiopathic epistaxis group had a self-limited groin hematoma and postembolization facial pain.CONCLUSION: Endovascular embolization of epistaxis is a safe procedure that can be useful for patients with severe acute epistaxis or chronic persistent bleeding. Patients who undergo endovascular embolization for epistaxis related to hereditary hemorrhagic telangiectasia require repeat embolization and subsequent surgical procedures more often than those with idiopathic epistaxis.